2021
DOI: 10.1002/mds.28519
|View full text |Cite
|
Sign up to set email alerts
|

Brain Damage and Gene Expression Across Hereditary Spastic Paraplegia Subtypes

Abstract: A BS TRACT: Background: Spinal cord has been considered the main target of damage in hereditary spastic paraplegias (HSPs), but mounting evidence indicates that the brain is also affected. Despite this, little is known about the brain signature of HSPs, in particular regarding stratification for specific genetic subtypes. Objective: We aimed to characterize cerebral and cerebellar damage in five HSP subtypes (9 SPG3A, 27 SPG4, 10 SPG7, 9 SPG8, and 29 SPG11) and to uncover the clinical and gene expression corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 37 publications
3
11
1
Order By: Relevance
“…Despite the lack of evidence of basal ganglia abnormalities on MRI in previous studies and in our MRI imaging [ 32 ], we observed nigrostriatal degeneration on the DAT-SCAN imaging, which could be related either to nigral degeneration or to dysfunction of the nigrostriatal synapses.…”
Section: Discussioncontrasting
confidence: 98%
“…Despite the lack of evidence of basal ganglia abnormalities on MRI in previous studies and in our MRI imaging [ 32 ], we observed nigrostriatal degeneration on the DAT-SCAN imaging, which could be related either to nigral degeneration or to dysfunction of the nigrostriatal synapses.…”
Section: Discussioncontrasting
confidence: 98%
“…Our observation of a rostro-caudal gradient of white matter volume decrease in SPG11 matches findings of previous studies: a frontal predominant decrease of fractional anisotropy was described in a study on 5 SPG11 patients [25]. Widespread and severe white matter damage was also observed in a combined VBM/DTI study on 24 SPG11 patients, with inverse correlations of ACE-R scores and fractional anisotropy for most tracts [15,26]. In this VBM-based analysis, cortical grey matter involvement was limited to motor regions and associative cortices whereas subcortical grey matter regions were predominantly affected.…”
Section: Artificial Intelligence Based Volumetry Patterns Of Cortical...supporting
confidence: 90%
“…Although increasing research has shown that SPG4-linked HSP is associated with cognitive dysfunction (Orlacchio et al, 2004 ; Murphy et al, 2009 ; Chelban et al, 2017 ; Akaba et al, 2021 ; Erfanian Omidvar et al, 2021 ; Giordani et al, 2021 ), the studies on its mechanism remain few. Brain abnormalities in regions including the cerebral cortex, corpus callosum, hippocampus, and thalamus were observed in patients with SPG4-HSP (Orlacchio et al, 2004 ; Murphy et al, 2009 ; Servelhere et al, 2021 ). In addition, mice with spastin depletion exhibited working and associative memory deficits and reduced function of hippocampal synapses (Lopes et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%